TRANSFORMASI DIGITAL DAN PENINGKATAN KESEJAHTERAAN MASYARAKAT PEDESAAN KAWASAN PEGUNUNGAN IJEN BANYUWANGI - Thita M. Mazya; Lala M Kolopaking; Dodik R Nurrochmat; Arif Satria; Irwan Irwan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2022)
The entry of digital technology into Banyuwangi's Ijen Crater Nature Park has resulted in numerous changes. Digital Technology or, information and communication technologies, have the potential to improve rural welfare.Rural ICTs, however, necessitates special efforts to develop suitable means for those who are unable to access the Internet or do not have the language capacity to understand the content. The aims of this study are to determine the extent to which digital technology penetration can promote transformation and improve the rural’s welfare. To assess the transformation and the level of welfare, a qualitative survey and analysis were conducted using 120 respondents household survey data . The findings show that villages have been able to reduce the digital divide and improve their quality of life, with a long-term positive impact on material well-being. This study demonstrates how digital technology can serve as a new source of social capital for rural sustainable developmen.